The man in the iron mask - DiCaprio, Leonardo; Irons, Jeremy, 1948-; Malkovich, John.; Dumas, Alexandre, 1802-1870.; Depardieu, Gřard, 1948-; Byrne, Gabriel, 1950-; Wallace, Randall (Santa Monica, Calif. : MGM Home Entertainment, 1998)
It is a time of both splendor and despair for the deeply divided French nation where the self-serving King Louis XIV enjoys the riches of the world while his people starve. Believing he is all-powerful, Louis fears no one - - except the one person who could bring an end to his absolute power: the man he condemned to wear an iron mask and imprisoned for life. But when the king's selfish excesses go too far, retired Musketeers Athos, Porthos and Aramis vow to free the mysterious prisoner who may be France's only hope for survival. Only one question remains : will their old comrade, the legendary d'Artagnan help them -- or destroy them?
Widescreen of full screen.
For specific features see interactive menu.
"Based upon the novel by Alexandre Dumas"--Container.
Produced by Randall Wallace, Russell Smith ; written for the screen and directed by Randall Wallace ; director of photography, Peter Suschitzky; editor, William Hoy; music, Nick Glennie-Smith.
Leonardo DiCaprio, Jeremy Irons, John Malkovich, Gerard Depardieu, Gabriel Byrne, Anne Parillaud, Judith Godreche.
Originally released as a motion picture.
Keywords: France -- History -- Louis XIV, 1643-1715 -- Drama; Films for the hearing impaired; Feature films; Adventure films; Historical films